2023
DOI: 10.3389/fpls.2023.1230023
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of biochar and chemical fertilizer on water and nitrogen dynamics, soil properties and maize yield under different irrigation methods

Lei Wang,
Shah Jahan Leghari,
Jiajun Wu
et al.

Abstract: Long-term application of nitrogen (N) fertilizer adversely degrades soil and decreases crop yield. Biochar amendment with N fertilizer not only can increase yield but also can improve the soil. A 3-year field experiment was conducted to determine the effect of biochar doses with N fertilizer on maize yield and soil N and water dynamics under border irrigation (BI) and drip irrigation (DI) methods. Treatments were 260 kg N ha−1 without biochar addition and combined with low, medium, and high doses of biochar, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Heavy reliance on N fertilizers to boost grain productivity compared to the past created tough challenges for both agriculture and environmental sectors. It has been identified that agricultural farming causes more pollution than any other source [49,50]. A recent study showed that fertilizer use increased by >30% in the past few years [51].…”
Section: Groundwater Degradationmentioning
confidence: 99%
“…Heavy reliance on N fertilizers to boost grain productivity compared to the past created tough challenges for both agriculture and environmental sectors. It has been identified that agricultural farming causes more pollution than any other source [49,50]. A recent study showed that fertilizer use increased by >30% in the past few years [51].…”
Section: Groundwater Degradationmentioning
confidence: 99%
“…Biochar can also increase soil enzyme and bacterial activities ( Muhammad et al, 2018 ; Effrey et al, 2019 ; Shen et al, 2019 ; Wan et al, 2023 ; Xiao et al, 2023 ). However, long-term single-use of biochar can also have drawbacks, such as reducing the effectiveness of plant nitrogen ( Bo et al, 2023 ; Wang et al, 2023 ; Zhang C. et al, 2023 ; Zhang N. H. et al, 2023 ; Zhang X. et al, 2023 ; Zhang Z. et al, 2023 ; Zheng K. et al, 2023 ; Li et al, 2024 ). In practice, biochar is commonly used with supplemental nutrients, such as organic fertilizer, to enhance soil quality, mitigate heavy metal stress, and increase crop productivity ( Muhammad et al, 2017 ; Saeed et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These advances correspond to the need to produce more food, decrease the volumes of imported maize (Hernández-López, 2022) and thus contribute to national food sovereignty (Padilla-Fidencio et al, 2022). On the other hand, work has been done to increase water use efficiency (Blankenagel et al, 2022), since this crop demands large volumes to generate high yields (Wang et al, 2023). Furthermore, there is not always correlation between high yield and high water use efficiency (Kresović et al, 2016).…”
Section: Introductionmentioning
confidence: 99%